COMPARATIVE ANALYSIS OF THE INFLUENCE OF FINANCIAL SECTOR INCLUSION AND DEVELOPMENT ON ECONOMIC GROWTH IN DEVELOPING COUNTRIES - Meisyari Meisyari; Hesniati Hesniati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze and compare the influence of the financial inclusion index and the financial development index on economic growth in developing countries. The main focus of this study is to find out whether the expansion of access to finance and the strengthening of the financial sector contribute significantly to the increase in economic activity. This study uses a comparative quantitative approach with panel data covering several developing countries during the period 2015 to 2021. Data was obtained from international institutions such as the World Bank, IMF, and Global Findex. The analysis was carried out by descriptive statistical test methods, correlation tests, and regression panel data using the Fixed Effect Model (FEM). The results of the study show that financial inclusion, especially from the physical side, such as the number of bank branches, has a significant positive influence on economic growth. In contrast, the financial development index shows a negative influence in some models, indicating that an increase in financial development does not necessarily have a direct impact on growth. These findings emphasize the importance of striking a balance between inclusion and strengthening financial institutions. Further research is recommended to explore the institutional and governance factors that mediate the relationship between the financial sector and economic growth.